Pemanfaatan Limbah Kulit Biji Mete sebagai Pupuk Organik untuk Meningkatkan Pertumbuhan Bibit Tanaman Mete - Sakinah, Nur; Djoefrie, Mochamad Hasjim Bintoro; ,, Hariyadi; Manohara, Dyah (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2014)
ABSTRACTCashew nut shells have not been fully utilized untill recently, and most of them are still in a form of wastes. Cashew nut shell wastes are organic matter containing macro elements that are useful for plants, such as N (0.84%), P (0.21%), K (0.70%), Ca (0.13%) and Mg (0.24%) that are useful for plants. Cashew nut shell wastes would be very potential if they were composted into organic fertilizers. The aim of this research was to analyze the effect of cashew nut shell compost formula application on growth and nutrient uptake of cashew seedlings. The research was conducted at IPB Teaching Farm Dramaga Bogor from November 2012 to May 2013. The experiment was arranged in randomized complete block design with 5 treatments and 3 replications. The results showed, that cashew nut shell compost formula application at 50 g polybag-1 and 100 g polybag-1 were significantly increased plant height, leaf number, stem diameter, roots length, fresh weight, dry weight of seedling, and N, P, K uptake at 3 months after planting (MAP) compared to no compost (top soil). The treatment of cashew nut shell compost formula at 50 g polybag-1 showed not significantly compared with goat manure at 100 g polybag-1 on the plant height, stem diameter, leaf number, roots length and N, P, K uptake at 3 MAP. Both of the treatment can improve the balance of nutrients in the soil thus enhancing the growth and vigor of cashew seedling. The treatment of cashew nut shell compost formula (50 g polybag-1) could replace the treatment of goat manure (100 g polibag-1) tended to increase cashew seedling growth.Keywords: A. occidentale L., bioactivator, cashew seedling, KBM compost